Migration in the Southern Balkans: From Ottoman Territory to Globalized Nation States - Vermeulen, Hans; Baldwin-Edwards, Martin; Boeschoten, Riki van (IMISCOE Research Series, 2015)
Migration; History, general; Cities, Countries, Regions; Demography